Visual persuasion of halal tourism on social media: the elaboration likelihood model perspective - Novita, Sophia; Pramudhita, Reinaldy Agung; Darmawan, Ferry (Jurnal Kajian Komunikasi, 2026)
Background: The rise of tourism-destination content on social media has also encouraged the development of halal tourism, which promotes Muslim-friendly destinations. The Elaboration Likelihood Model (ELM) has been widely used to explain the persuasion process in marketing and tourism communication, yet research integrating elements of visual persuasion, halal identity, and message-processing mechanisms in halal tourism promotion on social media remains limited. Purpose: This study aims to analyze the elements of visual communication that function as a persuasive mechanism in promoting halal tourism on social media from the perspective of ELM. Methods: This study employs a mixed-methods design with a sequential explanatory approach in two stages. The first stage is a content analysis. The second phase continued with a survey of social media users and was strengthened through semi-structured interviews with industry practitioners to integrate all findings. Results: The study shows that visual elements dominate halal tourism promotion on social media. Destination visuals appeared in 67.2% of content, followed by halal products or services (65.5%), influencers or tourist testimonials (63.8%), and religious symbols (62.1%). Meanwhile, halal certification only appears in 22.4% of content. The survey results showed that respondents highly recommended Islamic values in the promotion of halal tourism (M = 4.60), sharia tourism education (M = 4.40), Muslim cultural symbols (M = 4.38), and visualization of halal facilities (M = 4.19). Conclusion: Persuasion for halal tourism promotion on social media does not work effectively through central and peripheral channels separately. Visual elements, such as Islamic religious and cultural symbols, play a role in forming a Perceived Halal Identity that bridges the audience’s initial attention to an in-depth evaluation of the destination’s halal attributes. Implications: By proposing Perceived Halal Identity as a mediator between peripherals and central instructions, this study expands the ELM model in halal tourism communication.